FRACTAL DIMENSION OF THE RESISTANT AND SENSITIVE TO DOXORUBICIN BREAST CANCER CELLS, EXPOSED IN THE MAGNETIC FIELD - Gorobets, Oksana; Gorobets, Svitlana; Chekhun, Vasyl; Medviediev, Oleksandr; Berezin, Oleksandr; Garkavenko, Oleksandr (Proceedings of National Aviation University (archive), 2016)
In this paper the fractal dimension of the resistant and sensitive to doxorubicin MCF-line breast cancer cells, exposed in the magnetic field, is examined. It is revealed, that the resistant and sensitive to doxorubicin MCF-line breast cancer cells have different value ranges of the fractal dimension. Thereby, the main purpose of the present research is to check the possibility of using the fractal dimension as a marker for sensitivity determining of MCF-line breast cancer cells, exposed in the magnetic field.